Prillieuxina aporosae sp. nov. (Asterinales, Asterinaceae) from southern Western Ghats, India - Gokul, Gopinathan Nair; Thomas, Jacob; Mathew, Nisha (Phytotaxa, 2021)
A new species of the fungus Prillieuxina causing black mildew disease on Aporosa cardiosperma (Euphorbiaceae) is described and illustrated from Konni forest division of Kerala state, India. This is the first report of the genus Prillieuxina growing as a biotroph on host family Euphorbiaceae.